Hepatic resection for breast cancer related liver metastases: A single institution experience. (March 2022) - Reynolds, Ian S.; Cromwell, Paul M.; Walshe, Janice M.; Crown, John; Maguire, Donal; Geoghegan, Justin; Swan, Niall; Hoti, Emir
Background & objective: Liver resection for breast cancer liver metastases is becoming a more widely accepted therapeutic option for selected groups of patients. The aim of this study was to describe the outcomes of patients undergoing liver resection for breast cancer-related liver metastases and identify any variables associated with recurrence or survival. Methods: A retrospective review of a prospectively maintained database was undertaken for the 12 year period between 2009 and 2021. Clinicopathological, treatment, intraoperative, recurrence, survival and follow-up data were collected on all patients. Kaplan-Meier methods, the log-rank test and Cox proportional hazards regression analysis were used to identify variables that were associated with recurrence and survival. Results: A total of 20 patients underwent 21 liver resections over the 12-year period. There were no deaths within 30 days of surgery and an operative morbidity occurred in 23.8% of cases. The median local recurrence free survival and disease free survival times were both 50 months, while the 5 year overall survival rate was 65%. The presence of extrahepatic metastases were associated with a decreased time to local recurrence (p < 0.01) and worse overall survival (p = 0.02). Conclusions: This study has demonstrated that liver resection for breast cancer-related liver metastases is feasible, safe and associated with prolonged disease free and overall survival in selected patients. It is likely that this option will be offered to more patients going forward, however, the difficulty lies in selecting out those who will benefit from liver resection particularly given the increasing number of systemic treatments and local ablative methods available that offer good long-term results.